Barb Wilson letter to Thomas Kent regarding spring sightings, spring 1981 - Wilson, Barbara L.et al (1981)
Included with the letter is an annotated list of birds sighted and forms documenting the sighting of a Greater Scaup at the IPL Settling Ponds and Lake Manawa, and a Marbled Godwit and Ruddy Turnstone at Willow Slough. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1981. Epson - sheet feed